Ultralong telomeres shorten with age in nestling great tits but are static in adults and mask attrition of short telomeres. (4th April 2019) - Atema, Els; Mulder, Ellis; van Noordwijk, Arie J.; Verhulst, Simon
Abstract: Telomere length (TL) is increasingly being used as a biomarker of senescence, but measuring telomeres remains a challenge. Within tissue samples, TL varies between cells and chromosomes. Class I telomeres are (presumably static) interstitial telomeric sequences, while terminal telomeres have been divided in shorter (Class II) telomeres and ultralong (Class III) telomeres, and the presence of the latter varies strongly between species. Class II telomeres typically shorten with age, but little is known of Class III telomere dynamics. Using multiple experimental approaches, we show great tits to have ultralong telomeres, and we investigated age effects on Class II and III telomeres using a longitudinal approach (our method excludes Class I telomeres). In adults, TL averaged over the whole distribution did not significantly change with age. However, more detailed analyses showed that Class II TL did shorten with age, and, as in other species, the longest Class II telomeres within individuals shortened more quickly with age. In contrast, Class III TL did not shorten with age within individual adults. Surprisingly, we found the opposite pattern in nestlings: Class III TL shortened significantly with age, while the age effect on Class II TL was close to zero. Thus, Class III TL may provide information on developmental history, while Class II TL provides information on telomere dynamics in adulthood. These findings have practical implications for telomere studies and raise the interesting question of what causes variation in TL dynamics between chromosomes within individuals and how this is related to development.